2015
DOI: 10.1027/1016-9040/a000232
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Interventions for Children and Adolescents

Abstract: Abstract. This systematic review examines the meta-analytic evidence on four broad categories of preventive interventions for children and adolescents, including: mentoring, service learning, outdoor adventure, and social and emotional learning (SEL) programs. There were 15 meta-analytic studies that fit the criteria for inclusion. For each intervention type, the target population, main implementation strategies, and meta-analytic evidence are reported. The review considers the effectiveness of these preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 45 publications
3
30
0
1
Order By: Relevance
“…Youth mentoring programs involve pairing children or adolescents with adults, typically, volunteers, who are trained to provide friendship and support to mentees as well as be a positive role model and nurturer of mentees’ interests, skills, and hobbies. Although such programs are widespread, research on their effectiveness has revealed modest effect sizes and considerable room for improvement (DuBois, Portillo, Rhodes, Silverthorn, & Valentine, ; Gutman & Schoon, ). Match length has been demonstrated to be a key factor accounting for variability in both community‐based and school‐based mentoring program effects.…”
Section: Introductionmentioning
confidence: 99%
“…Youth mentoring programs involve pairing children or adolescents with adults, typically, volunteers, who are trained to provide friendship and support to mentees as well as be a positive role model and nurturer of mentees’ interests, skills, and hobbies. Although such programs are widespread, research on their effectiveness has revealed modest effect sizes and considerable room for improvement (DuBois, Portillo, Rhodes, Silverthorn, & Valentine, ; Gutman & Schoon, ). Match length has been demonstrated to be a key factor accounting for variability in both community‐based and school‐based mentoring program effects.…”
Section: Introductionmentioning
confidence: 99%
“…A review identified that the majority of children targeted for these interventions were aged 5 to 10 years (56%) and were classroom-based (74%) [ 9 ]. A review of meta-analyses of SEAL interventions concluded that high-quality SEAL programs can successfully increase children’s socioemotional and language skills, along with fostering positive outcomes and preventing negative ones [ 10 ]. When compared to other youth development programs offered to school-age youth, SEAL programs are among the most successful [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that successful mentoring programs are the primary intervention that can produce the most positive outcomes in at-risk youth (Kamosa-Hawkins, 2012;Gutman & Schoon, 2015). These authors defined "successful" as those programs that provide ongoing supervision, a consistent and caring bond between mentee and mentor, and longevity of the mentoring relationship (Gutman & Schoon, 2015).…”
Section: Mentoring Programs K-12mentioning
confidence: 99%
“…These authors defined "successful" as those programs that provide ongoing supervision, a consistent and caring bond between mentee and mentor, and longevity of the mentoring relationship (Gutman & Schoon, 2015). This is especially true for at-risk populations like those struggling in school, and at risk of dropping out of school.…”
Section: Mentoring Programs K-12mentioning
confidence: 99%
See 1 more Smart Citation